Intimate Infrastructures We Depend upon - Susanna Paasonen; Vilja Jaaksi; Anu Koivunen; Kaarina Nikunen; Karoliina Talvitie-Lamberg; Annamari Vänskä (Media Theory, 2023)
This essay takes on Lauren Berlant’s mapping of intimacy as ‘connections that impact on people, and on which they depend for living’ in order to address attachments, dependencies, and vulnerabilities in datafied contexts where digital platforms operate as infrastructures of everyday life. Building on interview material, we explore such intimate attachments as ones rife with friction and inconvenience, asking how vulnerabilities emerge and become differently distributed among our study participants. We argue that thinking about the datafied everyday in terms of intimacy opens up space for considering the fundamental ambiguities involved in what matters to people, what they are attached to, and what they simply need to live with. We further suggest that attending to the complexity and vitality of mundane relating, impacting, and world-making offers ways of exploring and techno-capitalist infrastructures of data extraction and mass surveillance in tandem with other attachments and connections that bind, and matter.